In-vitro drug release studies of chitosan-alginate nanoparticles loaded with non-volatile extracts of cymbopogon species - Rahman, Md Shamim; Sri Murugan, Sooriamoorthi; Amni, Nik Adnan; Raihana Zahirah, Edros; Siti Umairah, Mokhtar; Doolanea, Abd Almonem (International Scientific Organization, 2024)
The conventional topical dosage forms have plenty of drawbacks which cause patient inconveniences as well as treatment failure. To overcome these complications, drug design engineering is emphasizing on nanoparticle technology for its better drug carrier activity and targeted delivery in desired site of body. The objective of this study was to develop and evaluate topical formulation containing chitosan-alginate nanoparticles loaded with non-volatile extracts of Cymbopogon species. Among all of the test samples, nanoparticles loaded with 6 mg of extraction exhibited best entrapment capacity. This formulation successfully captured around 36.56% drug in nanoparticles. Thermo Gravimetric Analysis also showed thermal stability of the drug loaded nanoparticles. Furthermore, the formulation of nano cream that contained 6 mg of Cymbopogon sp. nanoparticles yielded the smallest nano-cream, with a particle size of 157.3 ± 20.80 nm. Using the basket dialysis approach, nanoparticle formulations loaded with 12 mg and 24 mg extracts showed a release rate of roughly 25%. On the other hand, the dialysis bag approach revealed that the drug released from the 24 mg of Cymbopogon sp. loaded in nanoparticles was about 37%. Lastly, the antioxidant study's findings indicate that cream-loaded nanoparticles containing 6 mg might be capable of scavenging radicals, with an IC50 value of 19.411g/ml. Chitosan-alginate nanoparticles loaded with Cymbopogon species exhibited significant drug release and antioxidant activity, indicating that this method could be useful for the formulation development of nanoparticles for skincare products.